2015
DOI: 10.1039/c4ce02207f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a metal–organic framework by octuple intercatenation of discrete icosahedral coordination cages

Abstract: Solvothermal reaction of the H 3 BTTC IJbenzo-IJ1,2;3,4;5,6)-trisIJthiophene-2′-carboxylic acid)) ligand with PbIJNO 3 ) 2 produced a unique 3-D polycatenated architecture that was constructed by octuple intercatenation of discrete icosahedral coordination cages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The resulting four‐connected non‐centrosymmetric diamondoid lattice ( dia net topology) is interlocked with a second lattice of the same type obtained by inversion (Figure and Supporting Information, Figure S5). A CSD survey showed that few coordination compounds crystallise in cubic space group Fd true3 c , but none of them contains two interlocked dia networks as in 2 . The structure exhibits three different types of disorder: 1) the 4‐pyridyl ring develops along a crystallographic threefold axis and consequently is disordered over three different positions; 2) a minority fraction [0.133(2)] of Fe 4 linkers is rotated by 60° around the Ag⋅⋅⋅Fe 4 ⋅⋅⋅Ag direction, with coinciding central ions (Fe1) but distinct peripheral metal centres (Fe2 and Fe2a), a feature already reported in the literature; 3) as found in few other isostructural Fe 4 compounds, the two dpm − ligands bonded to the same iron(III) ion adopt two different coordination modes: propeller‐like ( p ) and sandwich‐like ( s ); the p : s ratio is close to 60:40 and a complex distribution of Fe 4 isomers is therefore expected.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting four‐connected non‐centrosymmetric diamondoid lattice ( dia net topology) is interlocked with a second lattice of the same type obtained by inversion (Figure and Supporting Information, Figure S5). A CSD survey showed that few coordination compounds crystallise in cubic space group Fd true3 c , but none of them contains two interlocked dia networks as in 2 . The structure exhibits three different types of disorder: 1) the 4‐pyridyl ring develops along a crystallographic threefold axis and consequently is disordered over three different positions; 2) a minority fraction [0.133(2)] of Fe 4 linkers is rotated by 60° around the Ag⋅⋅⋅Fe 4 ⋅⋅⋅Ag direction, with coinciding central ions (Fe1) but distinct peripheral metal centres (Fe2 and Fe2a), a feature already reported in the literature; 3) as found in few other isostructural Fe 4 compounds, the two dpm − ligands bonded to the same iron(III) ion adopt two different coordination modes: propeller‐like ( p ) and sandwich‐like ( s ); the p : s ratio is close to 60:40 and a complex distribution of Fe 4 isomers is therefore expected.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most of the reported polycatenanes self-assembled from interlocked nanocages have used harsh conditions at high temperatures using solvothermal reactions under thermodynamic control 14 16 . Recently, it has been reported that the self-assembly of tris -pyridyl-benzene ( TPB ) , a very unexplored exo-tridentate ligand in the area of MOC and MOF chemistries 17 , and ZnCl 2 or ZnBr 2 with various aromatic solvents yields large single crystals of isostructural M 12 L 8 poly-[ n ]-catenanes where icosahedral M 12 L 8 nanocages with internal voids of ca .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the exceptional symmetric structures, this finds functional applications in areas such as molecular separation, catalysis, and emergent behavior because of their internal nanoconfined space. , One strategy to combine the structural properties of MOCs and metal–organic frameworks ( MOFs ) is by the preparation of poly-[ n ]-catenanes by mechanically interlocking metal organic cages through mechanical bonds . However, the synthesis of polycatenanes made of MOCs is not trivial because the cages need to have large windows where catenation can take place. The self-assembly of Platonic icosahedral MOCs is elusive with very few examples reported so far. , Even more rare are the so-called one-dimensional (1D) M 12 L 8 poly-[ n ]-catenanes which are formed by the interlocking of M 12 L 8 nanocages in one crystallographic direction. This is because enthalpic and entropic aspects play a crucial role in the self-assembly of such large host guest systems. , Using exo-tridentate 2,4,6-tris-(4-pyridyl)­pyridine ( TPP ) , or 2,4,6-tris-(4-pyridyl)­benzene ( TPB ) ligands and ZnX 2 (where X = Cl and I), a new class of poly-[ n ]-catenanes self-assembled with large M 12 L 8 icosahedral nanocages have been synthesized in solution. The π–π interactions arising from the aromatic central part of the ligands and the presence of aromatic templating solvents are crucial in the formation of the crystalline interlocked M 12 L 8 nanocages.…”
Section: Introductionmentioning
confidence: 99%